Molecular characterization of specialty mushroom germplasm of the National Mushroom Repository - Singh, S K; Yadhav, M C; Upadhyay, R C; Kamal, Shwet; Rai, R D; Tewari, R P (Mushroom Research, 2015)
Please see the full text